2015
DOI: 10.1111/aas.12523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single‐shot and steady‐state propofol anaesthesia on rocuronium dose–response relationship: a randomised trial

Abstract: CitationSt€ auble CG, St€ auble RB, Schaller SJ, Unterbuchner C, Fink H, Blobner M. Effects of single-shot and steady-state propofol anaesthesia on rocuronium dose-response relationship: a randomised trial. ActaBackground: Similar to volatile anaesthetics, propofol may influence neuromuscular transmission. We hypothesised that the administration of propofol influenced the potency of rocuronium depending on the duration of the administration. Methods: After consent, patients scheduled for elective surgery rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Intravenous anesthetics have no direct interaction with neuromuscular blockers, but etomidate (which has fewer cardiovascular effects) and ketamine (which acts on GABA receptors) may have indirect effects [ 72 73 ]. A single bolus dose of intravenous anesthetic (e.g., propofol) can decrease blood pressure and cardiac output, delaying the onset of action of NMBDs, but it also decreases muscle tone, which can accelerate the onset of action [ 74 ].…”
Section: Factors That Affect Muscle Contractilitymentioning
confidence: 99%
“…Intravenous anesthetics have no direct interaction with neuromuscular blockers, but etomidate (which has fewer cardiovascular effects) and ketamine (which acts on GABA receptors) may have indirect effects [ 72 73 ]. A single bolus dose of intravenous anesthetic (e.g., propofol) can decrease blood pressure and cardiac output, delaying the onset of action of NMBDs, but it also decreases muscle tone, which can accelerate the onset of action [ 74 ].…”
Section: Factors That Affect Muscle Contractilitymentioning
confidence: 99%
“…Similar results have been reported in other literature. A single shot of propofol and rocuronium shows that the potency of rocuronium is significantly enhanced after propofol infusion for 30 min compared with 2 min of propofol; this finding indicates that propofol can increase the affinity of rocuronium for the receptor under steady-state conditions [27]. Meanwhile, a randomized double-blinded trial found no statistically significant difference in the doses of propofol required for inducing anesthesia, regardless of whether the drug was administered as a freshly prepared propofol/lidocaine 10 : 1 mixture or as a separate injection after a dose of lidocaine [28].…”
Section: Discussionmentioning
confidence: 93%
“…However, the histamine levels were not measured in the present study, and no significant differences were observed in the number of dogs administered glycopyrrolate, atropine and vasopressor and inotropic drugs between groups. Regardless of the cause, arterial hypotension could have led to a potential decrease in blood pH due to tissue hypoperfusion, which could have slowed down the pH-dependent Hofmann degradation of cis-atracurium 22 27–29. In this case, more cis-atracurium would be available to shorten the NMB onset in dogs administered fentanyl and lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Potential electrolytes and acid-base alterations could not be excluded because they were not assessed in the present study. A longer NMB effect associated with hypotension could not be ruled out in dogs administered lidocaine 22 28 29. Finally, a potential haemodilution associated with an increased infusion rate of fluids could have prolonged the duration of action of NMB agents in the control group 46…”
Section: Discussionmentioning
confidence: 99%